Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/1356766721995983
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception and visit intention on Olympic destination: Symmetric and asymmetric approaches

Abstract: Tourists’ risk perceptions have been studied extensively in tourism literature and are considered an important factor influencing destination choice. However, despite the extensive research, many earlier studies using symmetric approaches have not adequately succeeded in addressing the contrarian case – high visit intention despite having negative perceptions. Therefore, this study utilised both symmetric and asymmetric approaches to address the effects of tourists’ perceptions (i.e. risk perception, image, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…Rahman et al, (2021) study added that due to the growth of the Covid19 outbreak, visitors' perceptions of travel risk and destination trust in hygiene and safety have a significant impact on their travel decisions. Choe and Kim (2021) examined the impact of perceived risk and destination perceptions on the intention to visit an Olympic destination. Their study demonstrated that the tourists' perceived risk alone is rarely the only cause for hesitation to travel.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Rahman et al, (2021) study added that due to the growth of the Covid19 outbreak, visitors' perceptions of travel risk and destination trust in hygiene and safety have a significant impact on their travel decisions. Choe and Kim (2021) examined the impact of perceived risk and destination perceptions on the intention to visit an Olympic destination. Their study demonstrated that the tourists' perceived risk alone is rarely the only cause for hesitation to travel.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In general, tourists make decisions based on perceptions and not facts (Carballo, León, and Carballo, 2017). Perception of risk is confirmed to have a significant effect on visiting decisions and tourist behavior (Karl et al, 2020;Choe and Kim, 2021). In another study, Liew (2022) also confirms that during the Covid-19 pandemic, there is a decline in interest in online hotel reservations, airline tickets, and company tourism package offers.…”
Section: The Correlation Between Perception Of Covid-19 Motivation In...mentioning
confidence: 92%
“…In the era of COVID-19, since many regions have precaution policies that have restrictions to travel, people’s normal travel preference is limited [ 2 ]. Furthermore, risk perception significantly influences tourists’ decision making in tourism choice [ 27 ]. Thus, the prospect theory is appropriate with the condition of COVID-19, in which extreme uncertainty generates fear [ 28 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%